Geological and geochemical implications of the genesis of the Qolqoleh orogenic gold mineralisation, Kurdistan Province (Iran) - Taghipour, Batoul; Ahmadnejad, Farhad (Geologos, 2015)
The Qolqoleh gold deposit is located in the northwestern part of the Sanandaj–Sirjan Zone (SSZ), within the NE–SW trending Qolqoleh shear zone. Oligocene granitoids, Cretaceous meta-limestones, schists and metavolcanics are the main lithological units. Chondrite-normalised REE patterns of the ore-hosting metavolcanics indicate REE enrichment relative to hanging wall (chlorite-sericite schist) and footwall (meta-limestone) rocks. The pattern also reflects an enrich-ment in LREE relative to HREE. It seems that the LREE enrichment is related to the circulation of SO42- and CO2-bearing fluids and regional metamorphism in the Qolqoleh shear zone. Both positive and negative Eu anomalies are observed in shear-zone metavolcanics. These anomalies are related to the degree of plagioclase alteration during gold minerali-sation and hydrothermal alteration. In progressing from a metavolcanic protomylonite to an ultramylonite, significant changes occurred in the major/trace element and REE concentration. Utilising an Al-Fe-Ti isocon for the ore-hosting metavolcanics shows that Sc, Y, K, U, P, and M-HREE (except Eu) are relatively unchanged; S, As, Ag, Au, Ca, LOI, Rb and LREE are enriched, and Sr, Ba, Eu, Cr, Co and Ni decrease with an increasing degree of deformation. Based on geochemical features and comparison with other well-known shear zones in the world, the study area is best classified as an Isovolume-Gain (IVG) type shear zone and orogenic type gold mineralisation. Based on the number of phases observed at room temperature and their microthermometric behaviour, three fluid inclusion types have been recognised in quartz-sulphide and quartz-calcite veins: Type I monophase aqueous inclusions, Type II two-phase liquid-vapour (L-V) inclusions which are subdivided into two groups based on the homogenisation temperature (Th): a) L-V inclusions with Th from 205 to 255°C and melting temperature of last ice (Tm) from -3 to -9°C. b) L-V inclusions with higher Th from 335 to 385°C and Tm from -11 to -16°C. Type III three-phase carbonic-liquid inclusions (liquid water-liquid CO2-vapour CO2) with Th of 345-385°C. The mean values of the density of ore-forming fluids, pressure and depth of mineralisation have been calculated to be 0.79-0.96 gr/cm3, 2 kbar and 7 km, respectively. The δ18Owater and δD values of the gold-bearing quartz-sulphide veins vary from 7.2‰ to 8‰ and -40.24‰ to -35.28‰, respectively, which are indicative of an isotopically heavy crustal fluid and likely little involvement of meteoric fluid. The δ18Owater values of the quartz-calcite veins have a range of -5.31‰ to -3.35‰, and the δD values of -95.65‰ to -75.31‰, which are clearly lower than those of early-stage quartz-sulphide-gold veins, and are close to the meteoric water line. Based on comparisons of the D-O isotopic systematics, the Qolqoleh ore-mineralising fluids originated from metamorphic devolatilisation of Cretaceous volcano-sedimentary piles. Devolatilisation of these units occurred either synchronously with, or postdates, the development of penetrative (ductile) structures such as shear zones and during overprinting brittle deformation